From Wall to Wall: How the Type 6 Secretion System Knows To Stop Growing - Ho, Brian T. (J Bacteriol, 2019)
There is an inseverable link between the size of a cell and the size of its subcellular components. The type 6 secretion system (T6SS) is no exception. In this issue, Stietz et al. report their analysis of the T6SS under conditions in which the cell size was altered to an extreme degree (M. S. Stietz, X. Liang, M. Wong, S. Hersch, and T. G. Dong, J Bacteriol 202:e00425-19, 2020, https://doi.org/10.1128/JB.00425-19). That study and others investigating the regulation of T6SS filament polymerization have provided insight into how the T6SS apparatus matches its size to the cell that contains it.